94.4k views
2 votes
If g(x) = x - 11, Find g(x) = -7

User Paparis
by
4.8k points

1 Answer

4 votes

By definition, the function is a relation in which each input value (x-value) has one and only one output value (y-value).

In this case, you have the following function:


g\mleft(x\mright)=x-11

And you need to find the input value that has the following output value:


g\mleft(x\mright)=-7​

In order to find that value of "x", you need to substitute the given ouput value into the function:


\begin{gathered} g\mleft(x\mright)=x-11 \\ -7=x-11 \end{gathered}

And now you must solve for the variable "x". To do it, you must apply the Addition property of equality by adding 11 to both sides of the equation:


\begin{gathered} -7+(11)=x-11+(11) \\ x=4 \end{gathered}

The answer is:


x=4

User Jay Stevens
by
4.5k points